State Role in Balancing Harmony in a Diversed Society: Regulating Religions in Indonesia - RS, Iza Rumesten (Brawijaya Law Journal, 2018)
As a State in which its society believes in the existence of God, it is not a surprising fact that a number of religions developand recognized in Indonesia. These include Islam, Catholic, Protestan, Hindu, Budha and Konghucu. Since most of Indonesian people are the followers of Islam, this religuions become the majority in Indonesia. Certain matters are regulated separately from the national laws, so that such laws only applicable for muslim. These include arrangement on marriage between moslem, which is provided by Indonesian Act Number 1 Year 1974 on Marriage. Indonesia also has a specific religious court for moslem. The competence of religious court for moslem is clearly stipulated in Article 1 paragraph (1) of Act Number 50 Year 2009 on Religious Courts. Article 49 of the Act stipulates that the religious courts have the duty and authority to examine, decide, and resolve cases in the first instance among Moslim in the field of marriage, inheritance, will, grant, waqaf, zakat, infaq, shadaqah and sari'ah economy.While some argues that the existance of religious court can be seen as Government failures in guarantee constitutional rights for minority, this paper seeks to find how to prevent potential religious disharmony in Indonesia. Based on the results of normative juridical research, it can be concluded that ideal arrangements related to religion is that it cannot separate the judiciary between Islam and other religions, because it might create possible sense of injustice and disharmony of minority religions. Thus, a specialized religious court for moslem might not be necessary.